Thermo-Electro-Elastic Friction Problem with Modified Signorini Contact Conditions (Journal of Nonlinear Modeling and Analysis, 2024)
The purpose of this paper is to investigate a frictional contactproblem between a thermo-piezoelectric body and an obstacle (such as a foundation). The thermo-piezoelectric constitutive law is assumed to be nonlinear.Modified Signorini’s contact conditions are used to describe the contact, andthese are adjusted to account for temperature-dependent unilateral conditions,which are associated with a nonlocal Coulomb friction law. The problem isformulated as a coupled system of displacement field, electric potential, andtemperature, which is solved using a variational approach. The existence of aweak solution is established through the utilization of elliptic quasi-variationalinequalities, strongly monotone operators, and the fixed point method. Finally, an iterative method is suggested to solve the coupled system, and aconvergence analysis is established under appropriate conditions.